TINJAUAN ATAS PROSEDUR PENCAIRAN DANA LANGSUNG (LS) GAJI PEGAWAI PADA DINAS PARIWISATA DAN EKONOMI KREATIF - Zahrah Widyaiswari Prasetyaningrum (2021)
Salary is a form of compensation for employees who work under the auspices of the agency, salary can also be one of the factors to improve employee performance that can support the achievement of an agency's goals. The purpose of this Final Project is to find out the procedure for direct disbursement of salary payments at the Dinas Pariwisata dan Ekonomi Kreatif. Procedures are steps in activities to achieve the main goals in an organized manner. In the process of direct disbursement of funds for this salary payment, what is done is making SPP - LS and SPM - LS salaries in the Finance Subdivision. When the funds will be disbursed, the SP2D is issued by the BPKD, the funds are disbursed through Bank DKI where the funds will go directly to the accounts of Civil Servants.